The Effects of Student Self‐Assessment on Learning in Removable Prosthodontics Laboratory. Issue 5 (1st May 2014) - Chambers, David W.; LaBarre, Eugene E.
Abstract : It has been consistently shown that there is a weak association between student self‐assessment and faculty member assessment of student projects in preclinical technique laboratory settings and that students overestimate their performance. Greater overestimation is observed among students judged by faculty to be the weakest, and these students also use a wider range of scores. This study hypothesized that student self‐assessment is a function of capacity to perform, accuracy of understanding grading standards, and psychological factors. Further it hypothesized that learning, defined as change in performance, is a function of ability and self‐assessment. Dental students at one U.S. dental school self‐assessed their performance on two projects in a removable prosthodontics laboratory course separated by a six‐month period. Faculty evaluations of these projects were used to determine students' understanding of the criteria for the projects, and a standardized psychological test was used to assess the learning orientation of the students. A statistical correction was made for the artifact of regression toward the mean. The study found that self‐assessment was a better predictor of future learning under these circumstances than was evaluation by faculty members.